Efficacy of cognitive behavioral therapy in children and adolescents with insomnia: a systematic review and meta-analysis - Ma,Zhong-Rui (2018)
Insomnia is highly prevalent in children and adolescents. However, the efficacy of cognitive behavioral therapy for insomnia (CBT-i) in children and adolescents remains controversial. Therefore, this systematic review and meta-analysis aimed to assess the efficacy of CBT-i in children and adolescents. We conducted a search of PubMed, EMBASE, the Cochrane Central Register of Controlled Trials, CINAHL, and PsycINFO to select primary studies evaluating CBT-i in children and adolescents that were primarily diagnosed through standardized diagnostic criteria. The primary outcomes of the meta-analysis included sleep onset latency (SOL), wake after sleep onset (WASO), total sleep time (TST), and sleep efficiency (SE%). Six randomized controlled trials and four open-label trials met all inclusion criteria. A total of 464 participants (ranging from 5–19 years of age) were included. Based on the results from sleep logs, a significant pooled effect size was observed for SOL and SE%. However, no significant pooled effect size was found for WASO or TST. Results from actigraphy were consistent with the sleep logs. A significant pooled effect size was observed for SOL and SE%, and no significant pooled effect size was found for WASO or TST. CBT-i might be effective in the treatment of children and adolescents with insomnia.